2003
DOI: 10.1242/jeb.00639
|View full text |Cite
|
Sign up to set email alerts
|

Transport mechanisms of diuresis in Malpighian tubules of insects

Abstract: SUMMARYWe have studied Malpighian tubules of Aedes aegypti using a variety of methods: Ramsay fluid secretion assay, electron probe analysis of secreted fluid, in vitro microperfusion and two-electrode voltage clamp. Collectively, these methods have allowed us to elucidate transepithelial transport mechanisms under control conditions and in the presence of diuretic peptides. Mosquito natriuretic peptide (MNP), a corticotropin-releasing factor (CRF)-like diuretic peptide, selectively increases transepithelial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(185 citation statements)
references
References 71 publications
3
179
0
3
Order By: Relevance
“…In addition, little is known of the effects of diuretic factors on ion transport across the posterior midgut. Mosquito natriuretic factor and leucokinin both stimulate fluid secretion by the Malpighian tubules (Beyenbach, 2003), and it would be of interest to determine the effects of these peptides on Na + transport across the posterior midgut. Letters denote significant differences between time points (ANOVA; P<0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, little is known of the effects of diuretic factors on ion transport across the posterior midgut. Mosquito natriuretic factor and leucokinin both stimulate fluid secretion by the Malpighian tubules (Beyenbach, 2003), and it would be of interest to determine the effects of these peptides on Na + transport across the posterior midgut. Letters denote significant differences between time points (ANOVA; P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Although the secretion of fluid and ions during diuresis have been studied extensively (reviewed by Beyenbach, 2003), relatively little is known of the patterns and mechanisms of inorganic ion transport across the posterior midgut during and after diuresis. Immunohistochemical studies have revealed the locations of the Na + /K + -ATPase, the V-type H + -ATPase in the adult midgut (Patrick et al, 2006), but the roles of these transporters in movement of ions across the midgut after the blood meal have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…As insect Malpighian tubules are fluid-secreting tissues, tubule ion transport pathways have been extensively mapped (Beyenbach, 2003;O'Donnell et al, 2003;Spring et al, 2009;Wieczorek et al, 2009), with tubules from D. melanogaster holding the distinction of being the fastest fluid-transporting epithelia known in biology (Maddrell, 2009). However, much more remains to be discovered, including neuroendocrine control of ion transport and fluid secretion (Coast, 2007).…”
Section: The Malpighian Tubules As Stress Sensorsmentioning
confidence: 99%
“…Imbibing a huge blood meal also quickly generates osmotic stress that requires an efficient excretory system for rapid removal of excess water (2)(3)(4)(5). However, one overlooked challenge of feeding on mammalian blood is the high temperature of the blood that rushes into the gut.…”
mentioning
confidence: 99%